The relation between parental involvement and school readiness: the mediating role of preschoolers' self-regulation skills - POLAT, ÖZGÜL (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2022)
This study investigates the relations between school readiness and self-regulation skills of preschool children and parental involvement towards education of their preschool children. More specifically, we focused on the mediation role of preschoolers' self-regulation skills on the relation between parental involvement and school readiness. The sample of the study includes 277 children, their parents (both mothers and fathers) and preschool teachers. Structural equation model was used to test the model. It is shown that the parental involvement and self-regulation skills are significantly related to children's school readiness. We also examined if self-regulation mediated the relation between parental involvement and school readiness and observed that the indirect effect of self-regulation skills from parental involvement to school readiness was not significant.
Keywords: Parental involvement; self-regulation skills; school readiness; preschool; CHILDRENS EFFORTFUL CONTROL; EXECUTIVE FUNCTION; EARLY-CHILDHOOD; EXTERNALIZING PROBLEMS; METACOGNITIVE SKILLS; AFRICAN-AMERICAN; EGO-RESILIENCY; AT-RISK; ACHIEVEMENT; KINDERGARTEN